Pharmacokinetics of Immediate and Sustained Release Cephalexin Administered by Different Routes to Llamas (Lama glama) - Verónica Kreil; Luis Ambros; Ana Paula Prados; Lisa Tarragona; Agustina Monfrinotti; Guillermo Bramuglia; Marcela Rebuelto (Advances in Pharmacological Sciences)
We investigate the pharmacokinetics of two different cephalexin formulations administered to llamas by the intravenous (IV), intramuscular (IM), and subcutaneous (SC) routes, the minimum inhibitory concentration (MIC) of cephalexin against some Escherichia coli and staphylococci isolated from llamas, and we apply the PK/PD modelling approach, so that effective dosage recommendations for this species could be made. Six llamas received immediate (10 mg/kg, IV, IM, and SC) and sustained (8 mg/kg IM, SC) release cephalexin. Pharmacokinetic parameters were calculated by noncompartmental approach. Immediate release SC administration produced a significantly longer elimination half-life as compared with the IV and IM administration (1.3±0.2 versus 0.6±0.1 and 0.6±0.1 h, resp.) and higher mean absorption time as compared with the IM administration (1.7±0.5 versus 0.6±0.4 h). Absolute bioavailability was in the range of 72–89% for both formulations and routes of administration. Cephalexin MIC90 values against staphylococci and E. coli were 1.0 and 8.0 μg/mL, respectively. Our results show that the immediate release formulation (10 mg/kg) would be effective for treating staphylococcal infections administered every 8 h (IM) or 12 h (SC), whereas the sustained release formulation (8 mg/kg) would require the IM or SC administration every 12 or 24 h, respectively.